Single cell analysis of tail regeneration in Ambystoma mexicanum - Echeverri, Karen (Trinity College (Dublin, Ireland). Department of Zoology, 2003)
This present study examined tail regeneration in the Mexican salamander Ambystoma mexicanum, on a single cell level in vivo. The primary aim of this study was to understand where the cells were coming from to replace all the lost structures when a tail is amputated.
Keywords: Zoology, Ph.D.; Ph.D. Trinity College Dublin